Pengaruh Adopsi Teknologi Informasi Pada Peningkatan Daya Saing Usaha Kecil Dan Menengah (Studi Pada UKM Di Wilayah Daerah Istimewa Yogyakarta) - Syarifah, Andimi Hana'; Fauziyah, Fauziyah (Universitas Muhammadiyah Yogyakarta, 2017)
Information technology adoption process much use the Technology Acceptance Model (TAM), which consists of three main variables, namely Perceived Ease Of Use, Perceived Usefulness and the Acceptance of IT. This study was followed by testing the extent to which the influence of the adoption of information technology to increase competitiveness companies especially in the SME sector. The analysis technique used is the SEM (Structural Equation Modeling) AMOS with respondents IT users working in the field of SME sector of the economy. Results showed that Perceived Ease of Use (PEOU) significantly influence Perceived usefulness (PU). Perceived Usefulness (PU) does not significantly influence IT acceptance. While Perceived ease of Use (PEOU) does not significantly influence IT Acceptance. In the end, IT Acceptance a significant effect on increasing SMEs competitiveness.